Governance quality and popular support for democracy in Africa - Mongae, Mmabatho (University of the Witwatersrand, Johannesburg, 2024)
The stability of democracy depends on citizens’ support for and satisfaction with democracy as a form of government. Yet the past decade has seen a public backlash against democracy worldwide, and Africa is no exception. This study aims to clarify the determinants of public perceptions of democracy, in particular how the quality of governance in African democracies affects public perceptions of democracy as a preferred system of government. Are citizens more likely to be supportive of and satisfied with democracy in countries that score higher on indicators of political and economic governance quality? This thesis addresses this question using a mixed methods approach. The study harnesses multi-level statistical analysis, incorporating national-level governance indicators from the Ibrahim Index of African Governance (IIAG), Varieties of Democracy (V-Dem), and Worldwide Governance Indicators (WGI), alongside individual-level survey data from Afrobarometer covering thirty-four African countries. The statistically selected case studies of Sudan, Botswana, South Africa, and Zimbabwe probe more deeply by capturing various experiences with democracy. The central finding is that public support for democracy in Africa depends significantly on the quality of governance. However, support for democracy is not based purely “instrumentally” on the receipt of material benefits, as citizens also value the practical provision of political freedoms and protections “intrinsic” to democracy. These findings challenge existing assumptions about the transactional nature of democratic support, highlighting the critical role of governance quality in fostering a deep-rooted commitment to democratic ideals. By foregrounding the lived experiences of African citizens within democratic systems, this thesis contributes to the discourse on democracy in Africa. It shifts the analytical lens from abstract institutional performance metrics to the tangible democratic encounters of individuals, providing a richer, more textured understanding of democratic resilience and support on the continent. Through this approach, the study not only responds to the existing gaps in literature but also offers fresh insights into the complex dynamics that underpin public attitudes towards democracy in Africa, thereby enhancing our understanding of the factors that promote or hinder democratic engagement and support
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy in International Relations, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Democracy; governance; Africa; public perceptions; SDG-11: Sustainable cities and communities